Study of the morphology and the adsorption behavior of molecularly imprinted polymers prepared by reversible addition-fragmentation chain transfer (RAFT) polymerization process based on two functionalized β-cyclodextrin as monomers - Asman, S.; Mohamad, S.; Sarih, N.M. (Elsevier, 2016)
The adsorption behavior of molecularly imprinted polymers (MIPs) prepared by reversible addition-fragmentation chain transfer (RAFT) polymerization process through the effect of polymer morphologies was described. In this study, two kinds of RAFT-MIPs were synthesized based on methacrylic acid functionalized β-cyclodextrin (MAA-β-CD) and 2-hydroxyethyl methacrylate functionalized β-cyclodextrin (HEMA-β-CD) monomers, represented as RAFT-MMIP and RAFT-HMIP, respectively. The results of RAFT-MIPs were respectively compared with MMIP and HMIP prepared by free radical polymerization (FRP) process (without RAFT agent). The Field Emission Scanning Electron Microscope (FESEM) images showed that the RAFT-MMIP had slightly spherical and spongy-porous structure, and the MMIP had rough surface structure. Besides, the surface area of RAFT-MMIP was larger than MMIP. In contrast, the RAFT-HMIP formed non-porous particles with a smooth surface structure, while the HMIP formed a porous structure with a large surface area size. Through their physical characteristics, it proved that the morphological properties played an important factor which affected the adsorption behavior properties of MIPs, including kinetic, isotherm and thermodynamic studies. The superior physical characteristics of RAFT-MMIP demonstrated the greater equilibrium contact time, fast kinetic adsorption, higher adsorption rate, enhanced adsorption capacity and higher binding affinity. However, the non-porous RAFT-HMIP structure was poor in the adsorption behavior system. The RAFT polymerization successfully worked depending on the monomer used to generate potential MIPs.